Peningkatan Kemampuan Membaca Kalimat Dengan Aksara Lampung Melalui Penerapan Model Pembelajaran Literasi Informasi Siswa Kelas Iv Sdn 04 Tanjung Aman Kotabumi Tahun Pelajaran 2020/2021 - Masitoh Masitoh (Edukasi Lingua Sastra, 2021)
The learning material in Lampung language is quite difficult to learn by elementary students. One of those were the material Lampung’s script reading. The teacher should be able to carry out the planning and learning experiences that will be provided to students properly. The teacher should be good at using a learning model that can improve students’ reading ability and motivation to learn Lampung’s script. One of those models that can be use by the teacher were information literacy learning model. The problem of this research is the improvement of students’ reading abilityto read Lampung’s script sentences through the implemenation of information literacy learning model at fourth grade students of sdn 04 Tanjung Aman Kotabumi in academic year2020/2021 The research objective was to describe the improvement of students’ reading ability to read Lampung’s script sentences through the implemenation of information literacy learning model at fourth grade students of sdn 04 Tanjung Aman Kotabumi in academic year 2020/2021 Classroom Action Research was applied in this research that devided into 4 steps, i.e; planning, implementing, observing and reflection. For the implementing steps was carried out in three cycle. Based on the implementation that already applied in this reserach, it could be conclude that the application of the information literacy learning model could improve the students learning process by reading Lampung’s script sentences. It could be seen based on the result as follows; (1) The precentage of the completeness of the assessment of the students’ ability to read Lampung’s script sentences in cycle I = 70% (22 students), cycle II = 85% (26 students), and cycle III= 98% (30 students). (2) The percentage of the model application of learning information in cycle I= 70%, cycle II= 83%, and cycle III= 95%.